IDNLearn.com makes it easy to find the right answers to your questions. Ask your questions and get detailed, reliable answers from our community of experienced experts.
Sagot :
To find the average rate of change of the function [tex]\( f(x) = -2x^3 + 4x^2 \)[/tex] from [tex]\( x = -1 \)[/tex] to [tex]\( x = 3 \)[/tex], we will follow these steps:
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = -2(-1)^3 + 4(-1)^2 \][/tex]
[tex]\[ f(-1) = -2(-1) + 4(1) \][/tex]
[tex]\[ f(-1) = 2 + 4 = 6 \][/tex]
2. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = -2(3)^3 + 4(3)^2 \][/tex]
[tex]\[ f(3) = -2(27) + 4(9) \][/tex]
[tex]\[ f(3) = -54 + 36 = -18 \][/tex]
3. Calculate the average rate of change using the formula:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
Here, [tex]\( x_1 = -1 \)[/tex] and [tex]\( x_2 = 3 \)[/tex], so:
[tex]\[ \text{Average rate of change} = \frac{f(3) - f(-1)}{3 - (-1)} \][/tex]
Substituting the values we computed:
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 - (-1)} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 + 1} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-24}{4} \][/tex]
[tex]\[ \text{Average rate of change} = -6 \][/tex]
So, the average rate of change of [tex]\( f(x) = -2x^3 + 4x^2 \)[/tex] from [tex]\( x = -1 \)[/tex] to [tex]\( x = 3 \)[/tex] is [tex]\(-6\)[/tex].
1. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = -1 \)[/tex]:
[tex]\[ f(-1) = -2(-1)^3 + 4(-1)^2 \][/tex]
[tex]\[ f(-1) = -2(-1) + 4(1) \][/tex]
[tex]\[ f(-1) = 2 + 4 = 6 \][/tex]
2. Evaluate [tex]\( f(x) \)[/tex] at [tex]\( x = 3 \)[/tex]:
[tex]\[ f(3) = -2(3)^3 + 4(3)^2 \][/tex]
[tex]\[ f(3) = -2(27) + 4(9) \][/tex]
[tex]\[ f(3) = -54 + 36 = -18 \][/tex]
3. Calculate the average rate of change using the formula:
[tex]\[ \text{Average rate of change} = \frac{f(x_2) - f(x_1)}{x_2 - x_1} \][/tex]
Here, [tex]\( x_1 = -1 \)[/tex] and [tex]\( x_2 = 3 \)[/tex], so:
[tex]\[ \text{Average rate of change} = \frac{f(3) - f(-1)}{3 - (-1)} \][/tex]
Substituting the values we computed:
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 - (-1)} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-18 - 6}{3 + 1} \][/tex]
[tex]\[ \text{Average rate of change} = \frac{-24}{4} \][/tex]
[tex]\[ \text{Average rate of change} = -6 \][/tex]
So, the average rate of change of [tex]\( f(x) = -2x^3 + 4x^2 \)[/tex] from [tex]\( x = -1 \)[/tex] to [tex]\( x = 3 \)[/tex] is [tex]\(-6\)[/tex].
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Your questions are important to us at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.